Sound to electric energy generating device - Maricel G. Dayaday; Jordan-James S. Olivo (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper presents the potential of an electromagnetic transducer device in a form of audio speaker that is used to capture sound waves to be converted into electricity. It is an interesting concept but less explored by researchers. The objective of the study is to measure the potential of electromagnetic transducer as a way to generate electricity. It deals with the creation of electricity through movement and magnetism. Sound waves can induce movement on the surface which in turn moves the transducer thus creating electricity. The source of sound was coming from an 8-inch subwoofer speaker with a frequency of 80 Hz that was held constant throughout the experiment. Furthermore, using simple linear regression analysis, the study showed that for every linear increase of sound intensity level and distance of the source, there is an exponential increase and an exponential decrease in the voltage root mean square (RMS) respectively. The functionality assessment of the device was statistically analyzed using completely randomized design. It was found that the energy level significantly increased as the sound intensity level increases given a fixed distance of 15 mm from the source. The device could generate enough energy to power small electronics such as light emitting diodes (LED), transistor and resistor.